The Influence of Burning Temperature of MIRHA On Mechanical Properties of Foamed Concrete - Bayuaji, Ridho (IPTEK Journal of Proceedings Series, 2014)
Microwave incinerator as one of the modern incinerators is proposed to produce amorphous Microwave incinerated Rice Husk Ash (MIRHA) with high pozzolanic reactivity thus can significantly enhance concrete properties. Analyses on the MIRHA with various burning temperature, the temperatures used were 300°C, 400°C, 500°C, 600°C and 800°C. To determine the physical and chemical properties of MIRHA with various burning temperature were also conducted through X-ray diffraction (XRD), X-ray Fluorescence (XRF), scanning electron microscope (SEM) and mechanical properties test. The results showed that the MIRHA at 300oC could be used as a cementitious material with optimum OPC replacement at 20%. It was found that MIRHA foamed concrete at 300oC achieved more than 100% higher strength compared to foamed concrete without MIRHA.